Bioaktivitas Metabolit Sekunder dari Genus Dipterocarpus - Nalle, Halena A.; Lulan, Theodore Y. K.; de Rozari, Philiphi; Ola, Antonius R. B. (Chemistry Notes, 2022)
Research has been conducted with the title "Literature Study of Secondary Metabolites and Bioactivity of Plants Genus Dipterocarpus". The method used is a descriptive method with the aim of being to find out the active compounds in the genus plant dipterocarpus and to know the ability of the bioactivity of genus plants dipterocarpus. Based on the results of the study, bioactivity of secondary metabolites from planst of the genus dipterocarpus namely antidiabetic, antiplasmodial, antibacterial, antioxidant, anticlasses, cytotoxic, anticholinesterase, antiproliferation, anti-inflammatory and antimicrobial. Very strong biosaltivity indicated by the ethyl acetate faction plant D. Intricatus Sagai Antioxidant IC50 Nialial is 0.075 μg / mL. While very weak bioacchables are shown extract methanol stem plant D. Costatus as cytotoxic with ic50 value 973 ± 14.57 μg / mL.